Quiz timer - 4 player / Mohd Nazrol Hisyam Sofian and Mahamad Salahudin Zainol Abidin - Sofian, Mohd Nazrol Hisyam; Zainol Abidin, Mahamad Salahudin (2003)
Quiz timer four players is used in quiz game, which use in program television. In this project most important component is ic cmos 4043 and 4078 is base operation' The process this circuit is four player and four switch where if one player 1 press the switch button 1 automatically the LED flash and a buzzer or relay is actives, the other players cannot press the button until the host press the reset button. For this project, we expect this circuit cannot only use for quiz timer four players, instead we can apply this circuit to another application like ‘open door detector for house and car’ and also for ‘bus ring’. Their operation is same like quiz timer, and we must have little modification for suitable on their operation. So we assume our project operation can be another application.